2012
DOI: 10.1007/s00330-012-2524-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose CT of the lung: potential value of iterative reconstructions

Abstract: Low-dose computed tomography is an important thoracic investigation tool. Radiation dose can be less than 1 mSv with iterative reconstructions. Iterative reconstructions render more low-dose lung CTs diagnostic compared to conventional reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 29 publications
(30 reference statements)
5
100
0
1
Order By: Relevance
“…The newest generation of CTs, in combination with iterative reconstruction techniques [14], allow for ultralow-dose CT acquisitions with effective doses similar to the dose of the topogram, and thus, not more than the dose with conventional thoracic radiography in two projections, which is 0.05-0.24 mSv [15]. These ultralow-dose CT acquisitions allow a high sensitivity and diagnostic confidence for the detection of pulmonary nodules [16].…”
Section: Introductionmentioning
confidence: 99%
“…The newest generation of CTs, in combination with iterative reconstruction techniques [14], allow for ultralow-dose CT acquisitions with effective doses similar to the dose of the topogram, and thus, not more than the dose with conventional thoracic radiography in two projections, which is 0.05-0.24 mSv [15]. These ultralow-dose CT acquisitions allow a high sensitivity and diagnostic confidence for the detection of pulmonary nodules [16].…”
Section: Introductionmentioning
confidence: 99%
“…6,7,15 This study demonstrates that half-dose CT images reconstructed using SAFIRE were superior to standard-dose images in regards to subjective im- This study found that the sharpness of the and another group selected S2 and S3, as the optimal strength levels for low-dose lung CT. 16,17,19 These differences may be influenced by body mass index (BMI), given that image noise is higher in patients with higher BMIs. 25 The mean BMI in previous studies is slightly higher than in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is a wide variation of dose-reduction results by using SAFIRE, [15][16][17][18][19][20][21] which makes it difficult to compare results. Differences might be partially explained by the inconsistency FIG 1. Boxplot diagrams.…”
Section: Discussionmentioning
confidence: 99%
“…Sinogram-Affirmed Iterative Reconstruction (SAFIRE) is a raw data and image domain-based 15 noise-modeling technique with 5 user-selectable strength levels. Previous work established the feasibility of SAFIRE for the study of body regions [15][16][17][18][19][20] and more recently in head CT 21 applications.…”
mentioning
confidence: 99%